The Competence of Teachers in Public TVET Institutions in the Khartoum State of Sudan: Challenges and Opportunities - Ahmed Mansour Mohammad Gasmelseed; Melaku Mengistu; Dawit Asrat (INVOTEC, 2022)
This study's primary purpose was to examine public institutions' TVET teachers' competence in Khartoum State and its challenges and opportunities. To this end, the study used an explanatory sequential mixed method design. The researchers used primary and secondary sources of data. The primary sources were students, teachers, managers, and directors whereas the secondary data were relevant policy documents. A total of 815 respondents from 12 TVET institutions were selected using stratified, simple random and purposive sampling. Data collection instruments were questionnaires semi-structured interview guide and Focus Group Discussions (FGD). Quantitative data were analyzed through descriptive (mean scores, standard deviation) and inferential statistics (one and two-sample t-test, one way ANOVA). The qualitative data were evaluated and interpreted with narration. The study found that one, teacher competence is sufficient. Two TVET teachers were effective and competent in their delivery of the training. There was no significant difference between teachers of different TVET institutions in their perceptions about teachers' competence. It recommended that the authorities: establish clear policies and strategies for TVET, allocate the necessary budget, and follow-up to carry out this plan; establish a partnership between industry and TVET to benefit students and compensate for training deficiencies, and be more concerned with teacher training and motivating them by providing their needs.